Valorization of banana peel by-product: An innovative component for gluten-free cookies rendered with corn flour - Panjit Pomasa; Samart Sai‐Ut; Sirima Sinthusamran; Chairat Techavuthiporn (Journal of Agriculture and Food Research, 2025)
Banana peels produce considerable amounts of waste during consumption and processing in the agroindustry. The preliminary study shows that ripened banana powder (RBP) is a beneficial source of natural antioxidants. This was shown by measuring its antioxidant activity with DPPH radical scavenging (DPPH-RS) (639.11 mg TE/100 g) and ABTS radical scavenging (ABTS-RS) (772.46 mg TE/100 g). This study aimed to investigate the feasibility of incorporating RBP into corn flour cookies as a viable ingredient for functional food products, considering its health benefits and gluten-free status. The cookies were enriched by substituting portions of the corn flour in the control formulation with varying levels of RBP: 0 % (C-0RBP), 3 % (C-3RBP), 6 % (C-6RBP), 9 % (C-9RBP), and 12 % (C-12RBP). Cookies provided with a substitution of up to 9 % RBP were found to be sensory-acceptable. Consequently, the physicochemical properties and storability of C-9RBP cookies were continuously examined in comparison with C-0RBP. The enrichment of cookies with RBP may improve their nutritional profile and bioactive properties, as evidenced by elevated levels of fiber and total phenolic compounds. The findings demonstrated a notable disparity in the cookie structures and functional groups between the two formulations, as evidenced by scanning electron microscopy and Fourier transform spectroscopy. The incorporation of RBP markedly improved the antioxidant activities of the cookies, as evaluated by DPPH-RS and ABTS-RS assays. The storability test indicated that C-9RBP exhibited lower peroxide value content and maintained a higher level of hardness relative to C-0RBP. The findings of this investigation suggested that RBP has the potential to serve as an alternative nutrient source, potentially contributing to human health by serving as a natural source of antioxidants. • The ripe banana peel (RBP) is an excellent source of antioxidants and fiber. • RBP fortification increased the amount of dietary fiber and antioxidants in corn flour cookies. • RBP-added cookies improved their structural integrity while decreasing their fracture strength. • RBP-added cookies had a decreased peroxide value and remained harder during storage.
Keywords: Seed and Plant Biochemistry; Food composition and properties; Sensory Analysis and Statistical Methods